PUBLIC ADMINISTRATION IN THE FIELD OF SUBSOIL USE: STRUCTURAL AND FUNCTIONAL ANALYSIS - Vlasenko, Sergiy (Public Management and Policy, 2026)
Within the framework of this article, a structural and functional analysis of public administration in the field of subsoil use in the postmodern period was carried out, according to which its essence was identified as a form of targeted state influence on the process of forecasting, discovery, use and protection of mineral deposits; the methodological and technological difference in the organizational and legal support of public administration in the field of reproduction of the mineral and raw material complex in the postmodern period was shown, on the basis of which the expediency of expanding the institutional and instrumental purpose of the state, which concerns not only the effectiveness of subsoil use, but also their protection, was substantiated; the structure of the functional system of the state in the field of mineral extraction and mineral use is investigated, which includes the determination of the functions of coordination, forecasting, control and regulation, which in their aggregate form the synergy of the target effectiveness of the process of rational use of subsoil; the role of the state as a provider and legislator of standards for standardizing the effectiveness of subsoil use by establishing structurally stable relations between subsoil users and state institutions is characterized; the tools for building a favorable “spatial-territorial structure” of subsoil use are investigated, which includes the construction of a holistic coordination process for forecasting mineral deposits, their discovery and tools for rational use from the point of view of realizing the security potential of the state.